Rancang Bangun Kendali Pintu Air Secara Otomatis Dengan Pemberitahuan Informasi Menggunakan SMS Pada Pengairan Persawahan Berbasis Mikrokontroller - Yulastri Yulastri; Anton anton; Ilhamdi ilhamdi (Elektron : Jurnal Ilmiah, 2018)
Indonesia is commonly known as a tropical country that is rich in biodiversity of flora and fauna which has fertile land and abundant natural products, especially in agriculture. Water is one of the most important elements in agriculture, particularly in rice fields. Normally the water source is coming from lakes, reservoirs, rivers, and from other water sources through waterways to rice fields. These water channels sometimes do not work properly because the sluices that opened manually are not fully open or partly open only so it makes water is not properly channeled to the rice fields. As a result, the farmers' harvest becomes a little, even experiencing crop failure. The automatic sluice control system on the rice field irrigation is a system that will control the paddy irrigation sluice in flowing water according to the conditions of the rice fields. This system uses an ultrasonic sensor to measure the water level in the field. Then the servo motor will move the sluice to open or close according to the readings of the water level from the sensor. Then the SIM800L GSM Module will send an SMS notification that the rice fields are lacking in water and the fields have been filled with water.